An investigation on relationship between process control parameters and weld penetration in robotic CO2 arc welding using factorial design approach - Chitrambalam, S. Thiru; Chew, Lai Huat; Phang, Boo Onn; Hemavathi, Sundaram; Mohammad, Imran Syakir; Mat, Shafizal (Penerbit Universiti Teknikal Malaysia Melaka, 2012)
Weld penetration is an important physical characteristic of a weldment that affects the stress carrying capacity of the weld joint. Several welding parameters seem to influence weld penetration. This paper presents the relationship between weld penetration and four direct welding process parameters of robotic CO2 arc welding process on structural carbon steel. Two level, full factorial design was applied to investigate and quantify the direct and interactive effects of four process parameters on weld penetration. The upper and lower limits of the process control variables were identified through trial and error methodology, and the experiments were conducted using ‘bead on plate’ mode. The performance of the model was then tested by using analysis of variance technique and the significance of the coefficients was tested by applying student’s‘t’ test. Commercial computer programs were used for statistical analysis. The main and interactive effects of different welding parameters are studied by presenting it in graphical form.